Efektifitas Pemberlakuan Sistem Satu Arah pada Jalan Indraprasta Kota Semarang dalam Rangka Pemerataan Sebaran Beban Lalu Lintas - Purwanto, Djoko; Eko Yulipriyono, EPF (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
The traffic problems in a big city such as Semarang generally caused by the typical situation like overcrowding at peak hours. To overcome this problem, Semarang Government has implemented “One Way System” on the Indraprasta Street section without providing road partner. This study is intended to identify the effectiveness of this policy. The following streets were reviewed: Indraprasta, Imam Bonjol, Mgr. Soegiyopranoto, and Pierre Tendean. Further, the intersections which studied are Indraprasta-Imam Bonjol-Pierre Tendean and Tugu Muda. Traffic survey data were collected in the morning and afternoon peak hours. Manual Kapasitas Jalan Indonesia 1997 was used in the data analysis procedure. This short-term study was conducted by simulating the proposed scenario and compared with the existing situations.In conclusion, “One Way System” on Indraprasta Street section is assessed not effective due to its relatively small degree of saturation, while Mgr. Soegiyopranoto Street has a large degree of saturation. Therefore, the one-way system to Imam Bonjol Street and Mgr. Soegiyopranoto Street also needed to implement and form a “rotary link“. In addition, enacting contraflow for public transport on Soegiyopranoto Street and Imam Bonjol Street is necessary, also the arrangement of signals and geometric in the intersection that linked those three streets.